Pengaruh Pendidikan Kesehatan Tentang Kanker Serviks Terhadap Perilaku Deteksi IVA Wanita Usia Subur di Desa Bilutan Rejosari - Puji Lestari; Tutik Rahayu; Sri Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Cervical cancer remains a major health problem among women dueto low awareness of early detection. The Visual Inspection with Acetic Acid (IVA) test is a simple and effective screening method. Health education is needed to improve understanding and encourage early detection behavior. Therefore, this study aimed to determine the effect of health education about cervical cancer on IVA detection behavior among women of reproductive age in Bilutan Rejosari Village. Method: This study employed a Quasi-Experimental design with a Pretest–Posttest Group Design. The study population consisted of 150 women of reproductive age (15–49 years). Samples were selected using purposive sampling, resulting in a total of 66 respondents. Result: a significant difference between IVA detection behavior scores before and after the intervention (p-value = 0.000). A p-value < 0.05 indicates that the health education provided regarding cervical cancer significantly improved IVA detection behavior among women of reproductive age in Bilutan Rejosari Village. Conclusion: Health education has a significant effect on improving early detection behavior of cervical cancer through the IVA examination.